Optimization of sintering temperature for the enhancement of pyroelectric properties of lead-free 0.88(Na 0.5 Bi 0.5 )TiO 3 –0.084(K 0.5 Bi 0.5 )TiO 3 –0.036BaTiO 3 piezoelectric ceramics - Mahdi, R.I.; Al-Bahnam, N.J.; Abbo, A.I.; Hmood, J.K.; Majid, W.H.A. (Elsevier, 2016)
Lead-free 0.88(Na0.5Bi0.5)TiO3–0.084(K0.5Bi0.5)TiO3–0.036BaTiO3 (BNT–BKT–BT) piezoelectric ceramics were prepared using the conventional mixed-oxide method with a sintering temperature range of 1120–1200 °C. The effect of the sintering temperature on the crystal structure, microstructure, and densification, as well as the dielectrics, piezoelectrics, and the pyroelectric properties of BNT–BKT–BT ceramics were investigated. Scanning electron microscopy and X-ray diffraction were used to study the microstructures of the sintered samples. The results showed that the increase in sintering temperature was very effective in improving both the density and electrical properties. However, the samples deteriorated when the sintering temperature was above the optimum. The BNT–BKT–BT ceramics exhibited an excellent structure and electrical properties at a 1180 °C sintering temperature. The density of the ceramics reached a maximum value of 5880 kg/cm3, which is about 98% of the theoretical density. The ceramic exhibited a pyroelectric coefficient of (p) 366 μC/m2 K, a piezoelectric coefficient of d33 = 183 pC/N, a remanent polarisation of Pr = 38.43 μC/cm2, a dielectric constant of ε′ = 933, a loss tangent (tan δ) of 0.0235, and the figure-of-merit for detection was (FD) of 15.408 μPa1/2. Improvement in the pyroelectric properties is crucial for the development of infrared detectors and sensors.